Patient-Centered Electroconvulsive Therapy Care: A Call to Action. Issue 2 (June 2016) - Coffey, M. Justin; Coffey, C. Edward
Abstract : Abstract: We present our experience applying the IOM's "10 Simple Rules" to our ECT Service at a major teaching hospital in order to achieve patient-centered care. We encourage all ECT providers to partner with their patients in engaging family members and significant others in each aspect of ECT care, especially the ECT treatment itself. Abstract : Supplemental digital content is available in the text.